Alexander Anderson, Abigail Hutchinson: A Young Woman Hopefully Converted - Hazard, Sonia (Conversations, 2014)
That “Protestants don’t have pictures” remains a common generalization. Yet in the early nineteenth century, nothing could be further from the truth. Protestant publishers like the nonsectarian American Tract Society (ATS) lavishly decorated their tracts with small but expressive printed illustrations.